Orientalism (Penguin Random House UK, 2019)
Surveys the history and nature of Western attitudes towards the East, considering orientalism as a powerful European ideological creation - a way for writers, philosophers and colonial administrators to deal with the 'otherness' of eastern culture, customs and beliefs.
English
Keywords: HM1041-1101 Social perception. Social cognition Including perception of the self and others, prejudices, stereotype